2019
DOI: 10.3889/oamjms.2019.262
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Profile in Children with Sepsis: Does Euthyroid Sick Syndrome Exist?

Abstract: BACKGROUND: Alterations in peripheral thyroid hormone metabolism play an eminent role in the development of the euthyroid sick syndrome. Altered solvation may also lead to changes in peripheral thyroid hormones. Data on thyroid hormones in critically ill children remain unclear. AIM: This study was aimed to evaluate thyroid hormone profile in children with sepsis as well as to assess the association between thyroid level and sepsis outcome. METHODS: An observational cohort study was conducted in 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Pikala Tarakeswara Rao et al ( 2019) 14 observed that Serum T3, T4, Free T3 and Free T4 levels were significantly lower among cases of neonatal sepsis as compared to gestational age matched control. Yanni G N et al (2019) 15 observed that Level of T3 and T4 were decreased on day 1 in pediatric sepsis. Of 80 subjects, 57 (71.2%) with low level T3 and 41 (51.2%) with low T4 were found.…”
Section: Discussionmentioning
confidence: 98%
“…Pikala Tarakeswara Rao et al ( 2019) 14 observed that Serum T3, T4, Free T3 and Free T4 levels were significantly lower among cases of neonatal sepsis as compared to gestational age matched control. Yanni G N et al (2019) 15 observed that Level of T3 and T4 were decreased on day 1 in pediatric sepsis. Of 80 subjects, 57 (71.2%) with low level T3 and 41 (51.2%) with low T4 were found.…”
Section: Discussionmentioning
confidence: 98%
“…That alteration is predominantly brought about by altered peripheral conversion of T4. Two researches before concluded that levels of FT3 and FT4 were lower in sepsis patients and animal models respectively [ 12 , 13 ]. The theories explaining the role of this phenomenon include the compensatory role in relation to the oxidative stress associated with acute disease [ 14 ], and the adaptive role—as an attempt to reduce energy consumption and protect against protein catabolism [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Our findings are consistent with previous studies that found thyroid function abnormalities (most commonly fT3) in adult patients who were hospitalized for respiratory failure requiring invasive mechanical ventilation, yet inconsistent with the prognostic role of fT3 as a risk factor for higher mortality risk in adult patients with low fT3. [15][16][17][18][19] Prior work has also concluded that NTIS occurs in 70 to 93% of critically ill patients as noted by a reduction in serum T3 values 14,20 as demonstrated by Yanni, et al 21 who also reported low T3 and T4 levels on the first and third days of ICU admission. Moreover, our results are also similar to those reported by Galusova, et al 22 for fT3 and TSH levels in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%